Comparative Analysis of Persuasive Strategies in English Social and Commercial Advertisements - Motallebi, Somayyeh; Kuhi, Davud (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The purpose of this paper is to investigate the difference between 35 social and 35 commercial ads that gathered through the internet. Socio-pragmatic strategies that used in ads including Grice (1975) cooperative principle (CP), Leech (1983) politeness principle (PP) and Searle (1970) speech act to persuade persuadees. The findings revealed that cooperative principles are mostly observed in both kinds of advertisement. And there was significant difference in social and commercial ads. This paper indicates that cooperative principles appear to be the more powerful constraints in advertising discourse than politeness principles. As well politeness principles are to be applied in commercial ads significantly more than in social ads. Speech acts are similarly observed in social and commercial ads and they are almost never violated.